2021
DOI: 10.3390/cancers13010149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes in Retinoblastoma beyond RB1: Findings from Next-Generation Sequencing

Abstract: This investigation uses hybridization capture-based next-generation sequencing to deepen our understanding of genetics that underlie retinoblastoma. Eighty-three enucleated retinoblastoma specimens were evaluated using a MSK-IMPACT clinical next-generation sequencing panel to evaluate both somatic and germline alterations. Somatic copy number variations (CNVs) were also identified. Genetic profiles were correlated to clinicopathologic characteristics. RB1 inactivation was found in 79 (97.5%) patients. All spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 52 publications
3
33
0
7
Order By: Relevance
“…Mutations included 4 small indels resulting in frameshift mutations and a large 588 Kb deletion disrupting the 5′UTR. This frequency is in line with previous reports of loss of function mutations in BCOR (10-23%) [18,[20][21][22]. Three patients, PD34259, PD37492 and PD37518 were male and since BCOR is located on chromosome X p11.4, these mutations were hemizygous in nature.…”
Section: Other Potential Driver Mutations Identified In Retinoblastomsupporting
confidence: 92%
See 2 more Smart Citations
“…Mutations included 4 small indels resulting in frameshift mutations and a large 588 Kb deletion disrupting the 5′UTR. This frequency is in line with previous reports of loss of function mutations in BCOR (10-23%) [18,[20][21][22]. Three patients, PD34259, PD37492 and PD37518 were male and since BCOR is located on chromosome X p11.4, these mutations were hemizygous in nature.…”
Section: Other Potential Driver Mutations Identified In Retinoblastomsupporting
confidence: 92%
“…Focal amplifications of the orthodenticle homeobox 2 gene (OTX2) were observed in 3% and focal deletions of the BCL6 Corepressor (BCOR) observed in 4% of the same cohort of retinoblastoma tumours [19]. Truncating point mutations in BCOR have been also reported in 10-17% of Rb [18,[20][21][22]. In addition, a number of studies have identified consistent large-scale copy number changes including gains of 1q, 2p and 6p and losses of 16q [19,20,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also supported the potential use of age at diagnosis as a risk factor for inherited RB. Recently, NGS is considered a highly sensitive and efficient approach for the detection of RB1 mutations due to increasing use of NGS in gene mutation analysis of RB; especially screening and identification of RB1 mutations with NGS substantially benefits the prepotency, early diagnosis and treatment of retinoblastoma (20)(21)(22)(23)(24)(25). Furthermore, the sensitivity rate of NGS in the present study was similar with that reported to previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…The combination of the aforementioned methods is essential for detecting all possible RB1 mutations (17)(18)(19). Recently, Next Generation Sequencing (NGS) has been implemented as rapid and effective strategy for identification of RB1 mutations since all variations can be detected in a single test, thus providing a number of advantages, including high sensitivity and cost-effectiveness (20)(21)(22)(23)(24)(25). In Vietnam, Sanger sequencing coupled with MLPA (SS-MLPA) could detect germline RB1 mutations in 82-84% of bilateral cases (26,27).…”
Section: Clinical Evaluation Of Rb1 Genetic Testing Reveals Novel Mutations In Vietnamese Patients With Retinoblastomamentioning
confidence: 99%